Weighing the importance of drivers’ workload measurement standardization - Pereira, Eduarda Manuel Barros (2019)
Workload is an inescapable topic within the context of Human-Machine Interaction (HMI). Evolution dictates that HMI systems will be all the more attractive to users the more intuitive they are. While attempting to create an optimized workload management system, the authors have encountered a difficulty in gathering a homogeneous definition of workload and a standardized manner of measuring it. In fact, some researchers even call into question the fact that maybe different things are being discussed. Could it be the underlying cause of many of the HMI failures so far recorded? Either way, the weight this concept carries is too heavy to be dealt lightly. It is very important that standardized strategies for measurement of workload are developed so that, for one, different results can be compared and contribute to a more robust understanding of the concept and that, for two, the measurement of workload is globalized and able to be adapted to all users.